Managing treatment resistance in schizophrenia: A joint study in Hong Kong and Singapore - Zheng, Shushan; Chan, Sherry Kit Wa; Lee, Jimmy (Frontiers in Psychiatry, 2022)
Objective: This study surveyed clinicians in psychiatry in Hong Kong and Singapore to understand their familiarity and prescribing practices in treatment-resistant schizophrenia (TRS) and clozapine-resistant schizophrenia (CRS). Methods: All clinicians in psychiatry in both regions were invited through email to participate in an anonymous online survey. The survey collected information on the participants’ characteristics, their familiarity and experience with clozapine use, and their treatment practices in TRS and CRS. Data collection took place between September 2019 and February 2020 in Hong Kong and December 2018 and March 2019 in Singapore. Results: 261 clinicians responded to the survey, with response rates of 19% (105 out of 556 participants) in Hong Kong and 50% (156 out of 309 participants) in Singapore. The majority of respondents (99.0% in Hong Kong; 87.9% in Singapore) were familiar with treatment guidelines for TRS. However, approximately half (54.2% in Hong Kong; 41.7% in Singapore) delayed the prescription of clozapine when indicated. In terms of alternatives to clozapine, approximately half or more of the clinicians in both regions would use high dose antipsychotics, long-acting injectable antipsychotics, antipsychotic polypharmacy, while the adjuvant use of mood stabilizers and electroconvulsive therapy differed between the two regions. In those with CRS, between 10-20% of the respondents added adjuvant mood stabilizers or antipsychotics, and 3-10% would use an antidepressant. Conclusion: Clozapine delays occur in spite of clinicians’ familiarity with treatment guidelines. More research is needed to guide the use of augmentation strategies and the search for effective treatments beyond clozapine.